2012
DOI: 10.3109/00016357.2012.680908
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reasons for extraction of crowned teeth: A prospective study at a university clinic

Abstract: Studies comprising other faculty clinics as well as general practices will be complementary in making more generalized statements regarding the etiology of extractions of crowned teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
18
1
1
Order By: Relevance
“…Periodontal breakdown of a crowned tooth structure is the most common reason contributing to tooth loss (59%) [6], other factors that http://dx.doi.org/10.1016/j.sdj.2014. 11.002 0377-5291/& 2014 Published by Elsevier B.V. n contribute to tooth loss or extractions include un-restorable teeth (either from fractures or caries) (27%), or periapical lesions (12%), however 35.6% of the teeth extracted had an endodontic treatment [6]. Anand et al reported on extraction trends in India, caries was observed as the main etiologic factor for extraction at 44%, periodontal breakdown at 33%, Orthodontic reasons at 11%, impactions and prosthodontics purposes were at 2% [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal breakdown of a crowned tooth structure is the most common reason contributing to tooth loss (59%) [6], other factors that http://dx.doi.org/10.1016/j.sdj.2014. 11.002 0377-5291/& 2014 Published by Elsevier B.V. n contribute to tooth loss or extractions include un-restorable teeth (either from fractures or caries) (27%), or periapical lesions (12%), however 35.6% of the teeth extracted had an endodontic treatment [6]. Anand et al reported on extraction trends in India, caries was observed as the main etiologic factor for extraction at 44%, periodontal breakdown at 33%, Orthodontic reasons at 11%, impactions and prosthodontics purposes were at 2% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as bleeding, deep probing, clinical attachment level increase and bone loss, eventually lead to tooth loss [5]. Periodontal breakdown of a crowned tooth structure is the most common reason contributing to tooth loss (59%) [6], other factors that http://dx.doi.org/10.1016/j.sdj.2014. 11.002 0377-5291/& 2014 Published by Elsevier B.V. n contribute to tooth loss or extractions include un-restorable teeth (either from fractures or caries) (27%), or periapical lesions (12%), however 35.6% of the teeth extracted had an endodontic treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…18 After periodontitis, tooth decay is the second most frequent reason for tooth loss with prosthetic crowns. 19 Furthermore, the use of crowns is also associated with the occurrence of caries in adjacent teeth. 20 …”
Section: Single-tooth Prosthesismentioning
confidence: 99%
“…Odds Ratio: 20,100 IC95% (7,188 -56,203) En el presente estudio se observó una relación estadís-ticamente signifi cativa entre la edad de los pacientes y la presencia de edentulismo total (tabla 7). Dikbas et al, coinciden con nuestros resultados, demostrando que las personas en un rango de edad de 55 a 64 años, están más propensas a las extracciones dentales (14). Por lo tanto, presentan una mayor recurrencia de edentulismo, al comparar con un grupo de edad entre los 35 y 44 años.…”
Section: Discussionunclassified